The Prognostic Value of Homocysteine in Acute Ischemic Stroke Patients: A Systematic Review and Meta-Analysis - Huang, Shengming; Cai, Jirui; Tian, Yuejun (Frontiers in Systems Neuroscience, 2021)
Background This comprehensive meta-analysis aimed to assess whether an increased homocysteine (Hcy) level is an independent predictor of unfavourable outcomes in acute ischaemic stroke (AIS) patients. Methods A comprehensive literature search was conducted up to August 1, 2020 to collect studies reporting Hcy levels in AIS patients. We analysed all the data using Review Manager 5.3 software. Results Seventeen studies with 15636 AIS patients were selected for evaluation. A higher Hcy level was associated with a poorer survival outcome (OR 1.43, 95% CI: 1.25–1.63). Compared to the AIS group, Hcy levels were significantly lower in the healthy control patients, with an SMD of 5.11 and 95% CI (1.87-8.35). Analysis of the different subgroups of AIS demonstrated significant associations between high Hcy levels and survival outcomes only in Caucasian and Asian patients. Moreover, whereas high Hcy levels were closely associated with gender, B12 deficiency, smoking, and patients who received tissue plasminogen activator treatment, no significant difference was found between increased Hcy levels and age, drinking, hypertension, diabetes mellitus, and hyperlipidaemia. In addition, the cut-off value (20.0µmol/L) might be an optimum cut-off index for AIS patients in clinical practice. Conclusion This meta-analysis reveals that the Hcy level may serve as an independent predictor for unfavourable survival outcomes in AIS patients, particularly in Caucasian and Asian AIS patients. Further studies can be conducted to clarify this relationship.